Regional ecosystem responses to environmental drivers in cold‐water lakes evaluated using stable isotopes of salmonid fishes - Matthew R. D. Cobain; Per‐Arne Amundsen; Åge Brabrand; Pär Byström; Jan G. Davidsen; Karl Ø. Gjelland; Jennifer E. Hansen; Ingeborg P. Helland; Trygve Hesthagen; Stein I. Johnsen; Roger I. Jones; Kimmo K. Kahilainen; et al. (Limnology and Oceanography, 2026)
Diverse environmental drivers influence food web energy and nutrient flows, a key ecosystem function, yet their relative importance remains poorly known. We compiled thousands of bulk stable isotope measurements (carbon and nitrogen) of brown trout ( Salmo trutta , n = 2854) and Arctic charr ( Salvelinus alpinus , n = 3062) from 120 cold‐water lakes across northern Europe, spanning 0.02 to 1090 km 2 in size, to quantify the relative importance of nine potential drivers of energy and nutrient flows. Fish community type and individual body size matched the well‐described ecologies of the two species: charr shifted from littoral to pelagic sources with interspecific competition, and trout opportunistically increased their trophic position with piscivorous prey availability and increasing body size. The anthropogenic impacts of water‐level regulation and catchment modification were mirrored in the two species, resulting in decreased δ 13 C values, implying increased relative pelagic production in regulated lakes, and increased δ 15 N values, possibly due to increasing cross‐boundary nutrient flows. Lake size and climatic drivers (summer precipitation and winter temperature) elicited strong species‐specific changes in isotope values, suggesting that predator‐driven ecological responses can dominate over ecosystem‐wide changes in energy and nutrient flows within lake food webs. No isotopic trends were observed with catchment productivity or shoreline complexity at the regional scale, contrasting with insights from local scale studies. This spatial mismatch suggests that environmental drivers of ecosystem processes playing out at the regional scale cannot necessarily be extrapolated from localized studies, despite correlated random lake effects capturing unexplained local baseline shifts in isotopes.

Combining green LiDAR bathymetry, aerial images and telemetry data to derive mesoscale habitat characteristics for European grayling and brown trout in a Norwegian river - Håkon Sundt; Knut Alfredsen; Jon Museth; Torbjørn Forseth (Hydrobiologia, 2022)
While many studies provide microscale relationships between fish and habitat characteristics, studies covering longer river reaches are scarce. Modern remote sensing techniques may enable new and effective ways of mapping and assessing mesoscale habitat characteristics. Using green LIDAR-derived bathymetry and hydraulic modelling, we tested how mesoscale depth and velocity were related to fish counts of adult European grayling ( Thymallus thymallus L.) and brown trout ( Salmo trutta L.) in 500 m river sections in three separate periods during the year. Using riverbank sinuosity from aerial images and a Froude number-based index from the hydraulic model as proxies for mesoscale spatial and hydraulic heterogeneity, we tested for temporal correlations with river section fish counts of adult European grayling and brown trout. Results showed that mesoscale mean depth and velocity were correlated to period fish counts of adult European grayling. Using mixed model analysis we found that riverbank sinuosity and the Froude number-based index were significantly correlated with river section occurrence of adult European grayling during spawning. The results can be used to assess how flow-induced changes and channel adjustments at the mesoscale level can influence access to and use of relevant habitats in rivers occupied by European grayling and brown trout.

Introduced European smelt (Osmerus eperlanus) affects food web and fish community in a large Norwegian lake - Antti P. Eloranta; Stein I. Johnsen; Michael Power; Kim M. Bærum; Odd Terje Sandlund; Anders G. Finstad; Sigurd Rognerud; Jon Museth (Biological Invasions, 2019)

Does flooding mitigation measures affect cladoceran and copepod communities in floodplain water bodies? - Thomas Correll Jensen; Bjørn Walseng; Jon Museth (Hydrobiologia, 2017)

The trophic niche of Arctic charr in large southern Scandinavian lakes is determined by fish community and lake morphometry - Odd Terje Sandlund; Antti P. Eloranta; Reidar Borgstrøm; Trygve Hesthagen; Stein I. Johnsen; Jon Museth; Sigurd Rognerud (Hydrobiologia, 2016)

Habitat use and diet of sympatric Arctic charr (Salvelinus alpinus) and whitefish (Coregonus lavaretus) in five lakes in southern Norway: not only interspecific population dominance? - Odd Terje Sandlund; Jon Museth; Tor F. Næsje; Sigurd Rognerud; Randi Saksgård; Trygve Hesthagen; Reidar Borgstrøm (Hydrobiologia, 2010)

The brown trout (Salmo trutta) in the lake, Øvre Heimdalsvatn: long-term changes in population dynamics due to exploitation and the invasive species, European minnow (Phoxinus phoxinus) - Reidar Borgstrøm; Jon Museth; John E. Brittain (Hydrobiologia, 2010)

Diet overlap between introduced European minnow (Phoxinus phoxinus) and young brown trout (Salmo trutta) in the lake, Øvre Heimdalsvatn: a result of abundant resources or forced niche overlap? - Jon Museth; Reidar Borgstrøm; John E. Brittain (Hydrobiologia, 2010)

The first record of the non-indigenous signal crayfish Pasifastacus leniusculus in Norway - Stein I. Johnsen; Trond Taugbøl; Oddgeir Andersen; Jon Museth; Trude Vrålstad (Biological Invasions, 2007)

Efforts to aid downstream migrating brown trout (Salmo trutta L.) kelts and smolts passing a hydroelectric dam and a spillway - Jo Vegar Arnekleiv; Morten Kraabøl; Jon Museth (Hydrobiologia, 2007)